Pemberhentian Anggota Kepolisian Republik Indonesia Pasca Putusan Pengadilan Negeri Jakarta Pusat Nomor: 46/Pid.Sus Tpk/2020/Pn.Jkt.Pst - Zulham Fandy Raharusun; John Dirk Pasalbessy; Dezonda Rosiana Pattipawae (Faculty of Law Universitas Pattimura, 2023)
In 2020, through a decision of the Central Jakarta Corruption Court (Tipikor) Number: 46/Pid.Sus-Tpk/2020/PN.Jkt.Pst NB, he was proven to have received bribes from the convicted corruption case Bank Bali Djoko Tjandra, then sentenced to 4 years in prison and until now still has the status of an active member of the Indonesian National Police. Review and analyze the status of NB as a member of the Indonesian National Police after the Decision Against NB after the Decision of the Central Jakarta District Court Number: 46/Pid.Sus-Tpk/2020/PN.Jkt.Pst and the legal consequences of the Implementation of Government Regulation Number 1 of 2003 concerning Termination of Members Police of the Republic of Indonesia Against NB After the Decision of the Central Jakarta District Court Number: 46/Pid.Sus-Tpk/2020/PN.Jkt.Pst. The research method used is normative juridical, using a statutory approach and a conceptual approach. The legal materials used in this paper are primary, secondary and tertiary legal materials. The research method used is normative juridical, using a statutory approach and a conceptual approach. The legal materials used in this paper are primary, secondary and tertiary legal materials.Until now the termination of members of the Indonesian National Police against NB has not been carried out by the Code of Ethics Commission, so that NB as a defendant through the Decision of the Central Jakarta District Court Number: 46/Pid.Sus-Tpk/2020/PN.Jkt.Pst is still an active member of the police.